Experimental ray-tracing: a precise and accurate method for the determination of the properties of optical systems - Maetz, Mischa; Traxel, Kurt (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 1999)
We developed a new technique to determine the impact position of single pencil beams in the image plane with an accuracy of 0.2 μm. This technique bases on the overlapping of secondary electron images from a 1000 mesh grid. The measurements themselves can be obtained without any change in the routine setup if a secondary electron counter is installed. By choosing different object positions (x0, y0) and divergence angles (θ0, ϕ0) for the pencil beam the characteristics of the used lens system can be analysed and the lens errors can be calculated with high precision. Results for the Heidelberg quadrupole doublet will be reported.